2009
DOI: 10.1084/jem.20082614
|View full text |Cite
|
Sign up to set email alerts
|

Milk fat globule epidermal growth factor–8 blockade triggers tumor destruction through coordinated cell-autonomous and immune-mediated mechanisms

Abstract: Carcinogenesis reflects the dynamic interplay of transformed cells and normal host elements, but cancer treatments typically target each compartment separately. Within the tumor microenvironment, the secreted protein milk fat globule epidermal growth factor–8 (MFG-E8) stimulates disease progression through coordinated αvβ3 integrin signaling in tumor and host cells. MFG-E8 enhances tumor cell survival, invasion, and angiogenesis, and contributes to local immune suppression. We show that systemic MFG-E8 blockad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 45 publications
3
74
1
Order By: Relevance
“…Mfge8 can regulate the differentiation of naive T cells into regulatory T cells (Tregs) and Th1 and Th17 cells (14)(15)(16). Each of these cell types has defined roles in asthma (17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…Mfge8 can regulate the differentiation of naive T cells into regulatory T cells (Tregs) and Th1 and Th17 cells (14)(15)(16). Each of these cell types has defined roles in asthma (17)(18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, systemic MFG-E8 blockade increases the effectiveness of conventional chemoradiotherapy and anticancer vaccines by augmenting apoptosis and potentiating DC-driven immunity. 117 Conclusions. The process of phagocytosis was discovered more than a century ago, much before the finer details of cell death regulation and mechanisms came to be described.…”
Section: Regulated Necrosismentioning
confidence: 99%
“…It has been shown that functionally blocking anti-MFG-E8 antibodies induced the regression of experimental breast cancers (Ceriani et al, 1987) and acted synergistically with conventional chemotherapy to reduce experimental colon carcinomas, melanomas and lymphomas (Jinushi et al, 2009); in addition, triple-negative breast cancer cells in which MFG-E8 expression was silenced were more sensitive to cisplatin treatment (Yang et al, 2011). Taken together with this published evidence, our present results support the idea that combinatorial therapies that include MFG-E8 blockade may be operative in the treatment of some breast cancer patients.…”
Section: Mfg-e8 Promotes Mammary Tumor Growthmentioning
confidence: 99%
“…Moreover, when these cells were injected in mice, MFG-E8 enhanced tumor growth through the inhibition of antitumor immune responses (Jinushi et al, 2008). In line with this, functionally blocking antibodies against MFG-E8 potentiated the effects of chemotherapeutic agents on experimental melanomas, colon carcinomas and lymphomas (Jinushi et al, 2009). In the mammary gland, MFG-E8 expression increases during pregnancy, lactation and subsequent mammary gland involution (Oshima et al, 1999;Hanayama and Nagata, 2005).…”
Section: Introductionmentioning
confidence: 96%